Onna: la rinascita di una comunità ferita dopo il terremoto - Giulia Spalla (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2010)
This article presents the author's experience at Onna camp, in Abruzzo, during the six months following the April 6th 2009 earthquake. Its purpose is to explain the role of psychologists in emergency scenarios. The article underlines the importance, in that kind of contexts, of interventions aimed at promoting people wellbeing by using the already existing community’s resources and the new resources that can develop within it, to stimulate internal processes that can fight back against the material, economical and social destruction. Therefore the psychologist, by operating within the emergency system as a mediator and facilitator of the complex relationships that develop inside and outside the emergency camp, plays an active role inside the community that is trying to rebuild itself. In the Onna case, through active listening, participative observation and analysis of the local cultural environment, the psychologists identified the emerging needs and promoted actions aimed at reactivating the liveliest aspects and resources of the community of Onna.